2006
DOI: 10.1093/chemse/bjj038
|View full text |Cite
|
Sign up to set email alerts
|

One-Trial Associative Odor Learning in Neonatal Mice

Abstract: Behavior genetics studies in mice demand efficient training protocols for rapid phenotypic screening. However, the capacity of neonatal mice to form and retain associative memories has been difficult to study due to their limited sensorimotor capacities. The present study describes a method for robust, naturalistic associative learning in neonatal mice as young as 3 days old. After removal of the dam from the home cage for 2 h, preweanling CD-1 mice of ages 3, 5, and 10 days postnatal were conditioned to assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 62 publications
0
46
1
Order By: Relevance
“…For example, Cook and Fagot (2009) showed that animals could learn hundreds of picture-response pairs after a single exposure and, more critical to our finding, that this form of one-trial learning was more robust when the to-be remembered pair was followed by a reward rather than by a mild penalty (Cook & Fagot, 2009). In contrast, our findings do differ from previous studies on associate learning that have found one-trial learning to be boosted by negative outcomes (Armstrong, DeVito, & Cleland, 2006;Bardo & Bevins, 2000). One critical difference, though, between the latter studies and ours (as well as Cook & Fagot, 2009) was the number of learned associations.…”
Section: Discussioncontrasting
confidence: 85%
“…For example, Cook and Fagot (2009) showed that animals could learn hundreds of picture-response pairs after a single exposure and, more critical to our finding, that this form of one-trial learning was more robust when the to-be remembered pair was followed by a reward rather than by a mild penalty (Cook & Fagot, 2009). In contrast, our findings do differ from previous studies on associate learning that have found one-trial learning to be boosted by negative outcomes (Armstrong, DeVito, & Cleland, 2006;Bardo & Bevins, 2000). One critical difference, though, between the latter studies and ours (as well as Cook & Fagot, 2009) was the number of learned associations.…”
Section: Discussioncontrasting
confidence: 85%
“…Thus far, 1-trial learning has been found with positive rewards involving single associations (4,6), but here our animals revealed a capacity to often learn in 1 trial when engaged in a much more demanding task requiring that thousands of randomly mapped and competing picture-response associations be learned and remembered. Earlier experiments examining learning set in primates bear some similarity with the present results.…”
Section: Discussionmentioning
confidence: 64%
“…monkey ͉ positive reinforcement ͉ fast mapping ͉ picture processing ͉ bird A long standing debate in educational settings concerns the relative efficacy of positive and negative outcomes in promoting learning and in dealing with the modification of problem behaviors (1,2) Despite the desirability of using positive rewards, the best animal evidence of rapid learning (i.e., 1-trial learning) come from experiments involving highly salient negative consequences, such as shock or illness (3)(4)(5)(6)(7). However, positive rewards may also have important effects on the speed of learning, because rewards have the advantage of directly communicating and confirming what an animal should do as opposed to what behavior should not be performed.…”
mentioning
confidence: 99%
“…As a rule, retention of the conditioned responses is very short in newborn mammals [23], although longer retention was obtained using food reinforcers [23] or resumption of maternal care after separation [24]. Because the primary aim of our study was to design a conditioning protocol suitable for high-throughput screening, we focused on the shortterm effects of conditioning, which proved consistent and easy to observe.…”
Section: Discussionmentioning
confidence: 99%